Breeze's blast - Bliss, Emily; Hanson, Sydney (2018)
Princess Breeze invites her human friend, Cressida, to attend the Blast, a festival featuring kite flying, but the wizard-lizard, Ernest, has blundered again and now giant bats sleep on the kites.
Keywords: Festivals -- Fiction; Kites -- Fiction; Bats -- Fiction; Unicorns -- Fiction; Princesses -- Fiction; Magic -- Fiction; Fantasy